Membrane Active Peptides Remove Surface Adsorbed Protein Corona From Extracellular Vesicles of Red Blood Cells - Singh, Priyanka; Szigyártó, Imola Cs.; Ricci, Maria; Zsila, Ferenc; Juhász, Tünde; Mihály, Judith; Bősze, Szilvia; Bulyáki, Éva; Kardos, József; Kitka, Diána; Varga, Zoltán; Beke-Somfai, Tamás (Frontiers in Chemistry, 2020)
Besides the outstanding potential in biomedical applications, extracellular vesicles (EVs) are also promising candidates to expand our knowledge on interactions between vesicular surface proteins and small-molecules which exert biomembrane-related functions. Here we provide mechanistic details on interactions between membrane active peptides with antimicrobial effect (MAPs) and red blood cell derived EVs (REVs) and show that they have the capacity to remove members of the protein corona from REVs even at lower than 5 uM concentrations. In case of REVs, the Soret-band arising from the membrane associated hemoglobins allowed to follow the detachment process by flow-Linear Dichroism (flow-LD). Further on, the significant change on the vesicle surfaces was confirmed by transmission electron microscopy (TEM). Since membrane active peptides, such as melittin have the affinity to disrupt vesicles, a combination of techniques, fluorescent antibody labeling, microfluidic resistive pulse sensing and flow-LD were employed to distinguish between membrane destruction and surface protein detachment. The removal of protein corona members is a newly identified role for the investigated peptides, which indicates complexity of their in vivo function, but may also be exploited in synthetic and natural nanoparticle engineering. Furthermore, results also promote that EVs can be used as improved model systems for biophysical studies providing insight to areas with so far limited knowledge.